KESALAHAN PEMAKAIAN EJAAN DALAM KARANGAN SISWA - Syamsul Ghufron (EDU-KATA, 2018)
This study aims to reveal the students' language error. The purpose of this study is focused on the description language errors contained in the writings of students and classify them by category of linguistics. To achieve these objectives conducted qualitative research with the steps: collecting data of students' language error and perform error analysis. The subjects were elementary school students in Lamongan. Data collection techniques used in the tests, refer to the technique, and technique noted. The result of the research indicates spelling errors in the form of (1) basic word writing, (2) vowel breathing on the base word, (3) expression and appearance / h /, (4) capital letter usage in name, (5) the capital letters at the beginning and middle of the sentence and the middle of the word, (6) prefix di- writing, (7) preposition writing, (8) abbreviation writing, (9) the writing of hyphens on the repeat word, and (10) the use of exclamation marks and question marks.